Adaptive-optics scanning laser ophthalmoscopy study of non-arteritic anterior ischemic optic neuropathy - Wenting Gu; Zizhong Hu; Weijie Chen; Qinghuai Liu; Yonghui Gu (Photodiagnosis and Photodynamic Therapy)
Objective: To investigate the changes in cone photoreceptors in patients with non-arteritic anterior ischemic optic neuropathy (NAION). Methods: Adaptive-optics scanning laser ophthalmoscopy (AO-SLO) was performed in patients with NAION and healthy participants. Acute NAION was defined as a disease duration of <2 months, whereas chronic NAION was defined as a duration of >2 months. We analyzed four quadrants (superior, inferior, nasal, and temporal with respect to the central fovea of the macula) of the cone layer images at 2.4° × 2.4° collected at 3° eccentricity. Patients with NAION were further examined by using optical coherence tomography (OCT). Results: Significant differences were observed in peripapillary retinal nerve fiber layer and ganglion cell layer thicknesses between the normal and affected eyes (P < 0.05). The AO-SLO data of patients with monocular NAION showed no statistical differences in the density, regularity, and dispersion of cone cells in the superior, inferior, nasal, and temporal quadrants (P > 0.05). No significant differences were noted in the density among the healthy, acute NAION, and chronic NAION groups (P > 0.05). Conclusion: AO-SLO showed cone integrity in patients with NAION. From a microscopic perspective, NAION might not affect cone photoreceptors.